Challenges of Modernity: Issue of Interest and Establishment of Modern Financial Institutions by Bosnian Muslims (1878-1918) - Kadrić, Edin (European Journal of Islamic Finance, 2024)
After five centuries of living under the Ottoman Empire, Bosnian Muslims lived under a non-Islamic empire’s governance in 1878. Life in a new environment brought numerous challenges and sparked debates, such as loyalty to a non-Islamic government, migration, and military service. One of the issues vehemently discussed was the issue of interest. The emergence of Islamic modernism, which sought to redefine the concept of interest (differentiating between interest and usury), did not find firm ground in the initial years of the 20th century in Bosnia and Herzegovina. However, a flexible interpretation of interest was offered according to the legal ruling (fatwa) specially issued for Bosnian Muslims by the central religious body of Muslims in the Ottoman Empire (Mashihat). Namely, interest was still considered prohibited (haram), but in the specific socio-economic circumstances in which Bosnian Muslims lived, it was declared permissible. The legal argument of necessity (darura) was used as the primary justification. This was a revolutionary step since this fatwa opposed conventional Islamic wisdom on interest and thus legitimized the establishment of modern financial institutions.